Investigation On The Properties Of Nanostructured Nickel Oxide Layer For Hydrogen Gas Sensor - Abubakar, Dauda (2018)
In this work, nanostructured NiO layers were synthesized using chemical bath deposition (CBD) and thermal oxidation methods for high performance of H2 gas sensor. The synthesis of nanostructured NiO layer was controlled base on severalgrowth parameters which were varied in each deposition methods. The structural, morphological, and optical properties of nanostructured NiO layer were studied using XRD, FESEM, EDX and UV-Vis spectrometer. The crystal size, surfaceroughness, porous surface, layer thickness, and crystallinity are factors that have great influence in enhancing the H2 gas sensing performance.